Ultrasound diagnosis of oropharyngeal squamous cell carcinoma and ultrasound evaluation of treatment efficacy (changes in tumor volume) - G. F. Allakhverdieva; G. Т. Sinyukova; V. N. Sholokhov; Т. Yu. Danzanova; О. А. Saprina; Е. А. Gudilina (Опухоли головы и шеи, 2019)
The study objective is to assess the capabilities of ultrasonography in the diagnosis of oropharyngeal squamous cell carcinomas and in the evaluation of treatment efficacy (changes in tumor volume).Materials and methods. This study included 98 patients (27 (27.5 %) females and 71 (72.5 %) males aged between 20 and 78 years with oropharyngeal tumors; of them, 12 (12.2 %) patients had recurrent tumors. Sixty-seven (68.4 %) participants had their tumors located in the tonsils; 31 (31.6 %) patients had tumors of the root of the tongue; 47 (48.0 %) patients presented with tumors invading adjacent tissues; 57 (58.2 %) patients had their lymph nodes involved. Thirty-two patients were operated at the first stage of treatment, whereas 66 (67.3 %) individuals received induction chemotherapy followed by sequential chemoradiotherapy. Treatment efficacy was evaluated 2 weeks following the completion of the second course of induction chemotherapy. We assessed tumor volume, its structure, type and intensity of vascularization, and the number and size of lymph nodes affected by metastasis. Ultrasonography findings were compared with the results of fibroscopy, X-ray computed tomography (CT) and magnetic resonance imaging (MRI) performed 2 weeks following the completion of the second course of induction chemotherapy (no later than 7–10 days).Results. The disagreement between histology and ultrasonography findings reflecting tumor volume (of either newly diagnosed or recurrent tumor) was statistically insignificant. The results of X-ray CT were more likely to be in agreement with histology than the ultrasonography results (85.0 % vs 70.0 %); however, this difference was not statistically significant. Data of X-ray CT and ultrasonography on the tumor volume demonstrated no significant difference between them. MRI and ultrasonography findings on the tumor volume were consistent in 50 % of cases. We identified the most common changes in the structure of the oropharyngeal tumors typical of positive and negative dynamics after 2 courses of induction chemotherapy. Patients with positive dynamics demonstrated a significant decrease in tumor volume detected by all diagnostic methods used (ultrasonography, X-ray CT, and MRI). There was a significant negative correlation between the efficacy of treatment assessed by ultrasonography and the grade of therapeutic pathomorphosis assessed by histology (r = –0.69; р = 0.0014).Conclusion. The accuracy of ultrasonography for the estimation of oropharyngeal tumor volume and its spread is comparable with that of X-ray CT and MRI. The disagreement between these methods was statistically insignificant. Ultrasonography is a more sensitive method for the evaluation of patient response to treatment than clinical data.